Psychometrics of the Concise Health Risk Tracking Self-Report (CHRT-SR16) Assessment of Suicidality in a Sample of Adults with Moderate to Severe Methamphetamine Use Disorder: Findings from the ADAPT-2 Randomized Trial - Trombello JM; Kulikova A; Mayes TL; Nandy K; Carmody T; Bart G; Nunes EV; Schmitz J; Kalmin M; Shoptaw S; Trivedi MH (Neuropsychiatric Disease and Treatment, 2023)
Joseph M Trombello,1 Alexandra Kulikova,2 Taryn L Mayes,1 Karabi Nandy,1,3 Thomas Carmody,1,3 Gavin Bart,4 Edward V Nunes,5 Joy Schmitz,6 Mariah Kalmin,7 Steven Shoptaw,7 Madhukar H Trivedi1 1Center for Depression Research and Clinical Care, Peter O’Donnell Jr. Brain Institute and Department of Psychiatry, University of Texas Southwestern Medical Center, Dallas, TX, USA; 2Department of Educational Psychology, University of North Texas, Denton, TX, USA; 3Peter O’Donnell Jr. School of Public Health, University of Texas Southwestern Medical Center, Dallas, TX, USA; 4Department of Medicine, University of Minnesota, Hennepin County Medical Center, Minneapolis, MN, USA; 5Department of Psychiatry, Columbia University Irving Medical Center and New York State Psychiatric Institute, New York, NY, USA; 6Faillace Department of Psychiatry and Behavioral Sciences, University of Texas (UT Health) at Houston, Houston, TX, USA; 7Department of Psychiatry and Biobehavioral Sciences, University of California Los Angeles, Los Angeles, CA, USACorrespondence: Madhukar H Trivedi, Center for Depression Research and Clinical Care, Peter O’Donnell Jr. Brain Institute and Department of Psychiatry, University of Texas Southwestern Medical Center, 5323 Harry Hines Blvd, Dallas, TX, 75390-9119, USA, Tel +214-648-0188, Fax +214-648-0167, Email Madhukar.Trivedi@utsouthwestern.eduBackground: The co-occurrence of suicidality and substance use disorders has been well established, but rating scales to examine suicidal behavior and risk are sparse among participants with substance use disorders. We examined the psychometric properties of the 16-item Concise Health Risk Tracking Scale – Self Report (CHRT-SR16) to measure suicidality among adults with moderate-to-severe methamphetamine use disorder.Methods: Participants (n = 403) with moderate-to-severe methamphetamine use disorder completed the CHRT-SR16 as part of a randomized, double-blind, placebo-controlled pharmacotherapy trial. The CHRT-SR16 factor structure was assessed using confirmatory factor analysis (CFA). Internal consistency was estimated with coefficients alpha (α) and omega (ω), test-retest reliability with intraclass correlation coefficient (ICC) and standard error of measurement, and convergent validity using Spearman’s ρ rank order correlation coefficient test between CHRT-SR16 factors and the Patient Health Questionnaire (PHQ-9). The analyses utilized baseline and week 1 data (for test-retest reliability only).Results: CFA revealed a seven-factor model of Pessimism, Helplessness, Social Support, Despair, Impulsivity, Irritability, and Suicidal Thoughts as the best-fitting model. The CHRT-SR16 also exhibited strong internal consistency (α = 0.89; ω = 0.89), test-retest reliability (ICC = 0.78) and convergent validity with the PHQ-9 total score (ρ = 0.62).Conclusion: The CHRT-SR16 showed strong psychometric properties in a sample of participants with primary methamphetamine use disorder.Clinicaltrials.gov Identifier: NCT03078075.Keywords: stimulant use disorder, confirmatory factor analysis, irritability, impulsivity, propensity, PHQ-9